Parenting self-efficacy mediates relationship between caregiving burden and parenting stress among parents of adolescents with disabilities: a cross-sectional study - Mundakir, Mundakir; Choliq, Idham; Sukadiono, Sukadiono; Vika , Ramadhana Fitriyani; Firman, Firman (Jurnal Ners, 2025)
Introduction: The study examines the role of parenting self-efficacy as a mediator in the relationship between caregiver burden and parenting stress. Methods: A cross-sectional study was conducted with 204 parents of children with disabilities. Data were collected using self-administered questionnaires, including the General Information Questionnaire, Zarit Burden Interview Questionnaire, Parenting Sense of Competence Scale (PSOC Scale), and Parenting Stress Index. Data analysis included multiple linear regression and Hayes’s PROCESS Macro. Results: The mean scores for caregiving burden, parenting self-efficacy, and parenting stress were 16.98 (SD = 10.10), 31.03 (SD = 6.72), and 61.72 (SD = 12.84), respectively. Parenting stress was negatively correlated with parenting self-efficacy (r = –0.35, p < 0.001). The findings reveal that caregiving burden significantly reduces parenting self-efficacy (B = −0.16, p < 0.001), which in turn lowers the ability of caregivers to manage stress (B = −0.48, p < 0.001). While caregiving burden has a direct effect on parenting stress (B = 0.07, p < 0.001), the total impact, including both direct and indirect influences, remains significant (B = 0.52, p < 0.001) with mediation percentages of 12.9%. Conclusions: The findings suggest that strategies to enhance parenting self-efficacy could significantly reduce the negative impact of caregiving burden on parenting stress. By improving self-efficacy, caregivers may better manage stress, highlighting the importance of targeted interventions that boost self-efficacy.